The risks in the use of the thoracic tape measure as a method of bovine weighing. Statistical analysis - Martínez Jiménez, Vanessa (2019)
The aim of this study was to evaluate if the methods of weighing Nellore cattle by digital scale (gold standard) and indirect by thoracic measurement are concordant applying the Lin’s Concordance Correlation Coefficient (CCC), the Bland-Altman Graph and the Survival Curve of the difference of the mean. The data of 46 steers reported in Watanabe et al. (2017) was analyzed applying these alternative methods. A greater average weight was observed in the measurements obtained with the digital scale, while the range obtained with the thoracic tape was greater, with an average difference between weights of 13.8 kg. In addition, the weight obtained with the digital balance has a minimum and median greater than that obtained by the thoracic tape. It was verified with the three methods that the measurements with the digital balance and the thoracic tape are not concordant for the weight data of Nelore steers. The measures present differences that make it impossible for these methods to be interchangeable, therefore, the calculation of the weight of Nelore cattle through the thoracic tape provides measures that can lead to erroneous conclusions.